Does Dual Plating for Distal Femur Fractures with Metaphyseal Comminution Results in Increased Stability and Early Fracture Healing: A Prospective Randomized Control Study - Ebin Jose; V Singaravadivelu; D S Anandan; S S Sailesh; Cheralathan Senguttuvan (Journal of Orthopedics and Joint Surgery)
Introduction: The treatment of distal femur fractures with metaphyseal comminution is often complicated by nonunion, varus collapse, and implant failure. The accepted standard of treatment is lateral plating with a distal femur-locking compression plate. The addition of an extra medial plate to the lateral plate provides more mechanical stability. We compared the radiological and functional outcome of these fractures following dual plating and lateral plating. Materials and methods: A total of 20 were selected and randomized and divided into two groups. The inclusion criteria were all distal femur fractures with metaphyseal comminution. Gustilo-Anderson type IIIB and type IIIC fractures were excluded from the study. Dual plating was done in the first group by two approaches, lateral and subvastus approach, while lateral plating was done in the second group by the lateral approach. Patients were followed up for 2 years. Radiological and functional outcomes were assessed on follow-up. Result: There was a statistically significant difference in average time for radiological union, which was 13 weeks in the dual plating group and 28 weeks in the lateral plating group (p-value = 0.038). Patients with dual plating had early weight bearing. There was no significant difference in functional outcome between both groups. Conclusion: Dual plating for distal femur fractures with metaphyseal comminution results in an early radiological union and early weight bearing and allows an early return to work.